Private Military Contractors in Africa: The Case of Erik Prince - Aty, Mourad; Elaggoune, Abdelhak (Africana Studia, 2020)
Erik D. Prince, a prominent figure in the private military industry, has been under scrutiny for almost two decades now. From Blackwater, the notorious company he created by late 1990s to the Controversy of the Trump Transition Team and Russia connections, Prince has set a plan for Africa at some time during this period. Private military contractors provide a plausible denial for state actors to avoid the political cost in cases where the loss of lives within the operating personnel is highly expected. The unstable and weak states with no political traditions in peaceful transition of power are the favorite arena for international powers to exert their influence and attempt to have foothold there; they are all in a scramble for the region. This paper provides an understanding of the nature of the private military industry in Africa with a major focus on Erik Prince.